Local Bifurcation of Four Species Syn–Ecosymbiosis model - Abbas Majeed, Azhar (Iraqi Journal of Science, 2023)
In this paper, the conditions of occurrence of the local bifurcation (such as saddle-node, transcritical and pitchfork) near each of the equilibrium points of a mathematical model consists from four-species Syn- Ecosymbiosis are established.